Persistent Mullerian duct syndrome: a rare cause of unilateral cryptorchidism - Keukens, Laura (BMJ Publishing Group, 2012)
Persistent Mullerian duct syndrome (PMDS) is a rare syndrome and sometimes the cause of a common problem in paediatric and surgical practice, namely undescended testes. PMDS is a recessive disease in which there is a defect in anti-Mullerian hormone secretion or receptor activity resulting in persistence of Mullerian structures such as a uterus or fallopian tubes with otherwise normal virilisation. Here the authors present a case of a 1½-year-old boy who was referred to their hospital because of unilateral cryptorchidism. During laparoscopic surgery, two gonads were present joined together by a uterus-like structure. Additional investigations showed a normal male karyotype and biopsies of the gonads revealed infantile testis parenchyma making the diagnosis PMDS likely.